Pelatihan Pengelolaan Sampah Plastik Menjadi Produk Kreatif Bernilai Ekonomis Di Desa Senyiur - Abdurrahim; Samsul Hadi; Muhammad Hanafi; Syamsur Rizal; Sukranudin; Irwan Yon Hadi; Nasrullah (Indonesia, 2023)
Plastic waste management in Senyiur Village faces significant challenges, particularly due to limited knowledge and inadequate facilities. This study aims to educate the community on plastic waste processing through circular economy-based training. The methodology involves active participation from housewives and local youth in technical training, such as waste sorting, converting waste into creative products, and understanding marketing. Data were collected through direct observation and interviews, with qualitative data analysis. The results show an increase in community skills in processing plastic waste, the formation of a waste management community, and enhanced environmental awareness. Furthermore, the training successfully created new business opportunities, contributing to household economic improvement. In conclusion, community-based and active participation approaches have proven effective in addressing environmental issues while improving economic welfare in Senyiur Village, and can serve as a model for other villages facing similar challenges.